2014
DOI: 10.1158/0008-5472.can-14-0385
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Fatty Acid Analogues Suppress Breast Tumorigenesis and Progression

Abstract: Obesity and type 2 diabetes (T2D) are associated with increased breast cancer incidence and mortality, whereas carbohydrate-restricted ketogenic diets ameliorate T2D and suppress breast cancer. These observations suggest an inherent efficacy of nonesterified long-chain fatty acids (LCFA) in suppressing T2D and breast tumorigenesis. In this study, we investigated novel antidiabetic MEDICA analogues consisting of methyl-substituted LCFA that are neither b-oxidized nor esterified to generate lipids, prompting int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…The striking feature of the work done to date in a number of model systems using different dietary interventions is that alterations in metabolism have a far reaching effect on tumor cells, tumors and the tumor microenvironment. Studies have shown reductions in growth rate as one might expect however, there are also changes in the formation of reactive oxygen species and oxidative stress (Stafford et al, 2010; Milder and Patel, 2012; Allen et al, 2013), angiogeneisis (Zhou et al, 2007; Jiang and Wang, 2013; Woolf et al, 2015), hypoxia (Maurer et al, 2011; Poff et al, 2015; Woolf et al, 2015), inflammation and peri-tumoral edema (Mavropoulos et al, 2009; Woolf et al, 2015), metastasis and invasion (Gluschnaider et al, 2014; Lv et al, 2014; Hao et al, 2015; Poff et al, 2015) and the expression of various transcriptional and post-transcriptional modulators such as NF-κB (Woolf et al, 2015) and microRNAs (Pazmandi et al, 2015). …”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…The striking feature of the work done to date in a number of model systems using different dietary interventions is that alterations in metabolism have a far reaching effect on tumor cells, tumors and the tumor microenvironment. Studies have shown reductions in growth rate as one might expect however, there are also changes in the formation of reactive oxygen species and oxidative stress (Stafford et al, 2010; Milder and Patel, 2012; Allen et al, 2013), angiogeneisis (Zhou et al, 2007; Jiang and Wang, 2013; Woolf et al, 2015), hypoxia (Maurer et al, 2011; Poff et al, 2015; Woolf et al, 2015), inflammation and peri-tumoral edema (Mavropoulos et al, 2009; Woolf et al, 2015), metastasis and invasion (Gluschnaider et al, 2014; Lv et al, 2014; Hao et al, 2015; Poff et al, 2015) and the expression of various transcriptional and post-transcriptional modulators such as NF-κB (Woolf et al, 2015) and microRNAs (Pazmandi et al, 2015). …”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…For example, Gluschnaider et al used the MMTVPyMT oncomouse model to demonstrate that a KD suppressed breast tumor growth (Gluschnaider et al 2014). Likewise, Allen et al showed that the KD enhanced radiation and chemotherapy responses in a mouse lung xenograft model by increasing oxidative stress in both NCI-H292 and A549 lung xenograft models (Allen et al 2013).…”
Section: Kd In Other Cancersmentioning
confidence: 99%
“…For example, Gluschnaider et al used the MMTV-PyMT oncomouse model to demonstrate that a KD suppressed breast tumor growth (Gluschnaider et al 2014). For example, Gluschnaider et al used the MMTV-PyMT oncomouse model to demonstrate that a KD suppressed breast tumor growth (Gluschnaider et al 2014).…”
Section: Kd In Other Cancersmentioning
confidence: 99%